Mixed Type Reverse Order Law for the Core Inverse in \(C^*\)-Algebras - Krishnaswamy, D.; Selvi, V. (Communications in Mathematics and Applications, 2021)
In this paper, several equivalent conditions related to the reverse order law for the core inverse in \(C^*\)-algebras has been determined.